Pengaruh Struktur Organisasi dan Pengendalian Internal Terhadap Kualitas Sistem Informasi Akuntansi Manajemen Pada PT. Agrabudi Jasa Bersama - Melly Refita (Akuntansi, 2024)
The development of information technology has changed the way companies manage accounting information. Before computers and computerized systems, management accounting information was collected and processed manually, so it took longer than using computerized systems. One of the companies that has shifted accounting operations from a manual system to a computer system is PT. Agrabudi Jasa Bersama. The purpose of this study is to find out whether organizational structure and internal control affect the quality of management accounting information at PT. Agrabudi Jasa Bersama. The research method used in this study is quantitative research with a quantitative descriptive approach. The sample in this study was selected by a saturated sampling technique where all populations in this study were sampled. The total sample used in the study was 33 employees of PT. Agrabudi Jasa Bersama. The tests carried out in this study are multiple linear regression which includes research instrument tests, classical assumption tests and hypothesis tests. The results of research conducted at PT. Agrabudi Jasa Bersama obtained the results that the organizational structure and internal control have a significant influence partially or simultaneously on the quality of the management accounting information system at PT. Agrabudi Jasa Bersama.